Participant Expectations in Pulmonary Hypertension–Related Research Studies. (1st June 2015) - Gray, Michael P.; Aldrighetti, Rino; Fagan, Karen A.
Abstract : The Pulmonary Hypertension Association (PHA) is a patient advocacy organization seeking to find ways to prevent, improve treatment for, and cure pulmonary hypertension (PH) and to provide hope for the PH community through support, education, research, advocacy, and awareness. Many patients involved with PHA are also involved in various PH‐specific research studies; however, the patient expectations and priorities for PH‐specific research are currently unknown or not well examined. Our objective was to identify the current modes of study entry, priorities within research, and expectations over the course of study involvement for patient constituents of PHA. A 29‐question online survey was designed by PHA and disseminated to the PHA patient constituency on its Facebook page through a post on November 29, 2012. Responses were collected on SurveyMonkey through December 10, 2012. Respondents were divided into parallel survey tracks, depending on whether the respondent indicated previous participation in research studies. These two cohorts of individuals were analyzed and, where appropriate, compared with tests of association. A total of 234 respondents were included in the final data analysis, with 95 (40.6%) reporting previous participation in research studies. These respondents reported an overall positive experience in their research studies (64.9% very good, 21.3% good, 12.8% neutral, 1.1% bad). Of the respondents with previous research study participation, 91.1% indicated that receipt of the study outcome after participation would positively influence their decision to participate in future research; despite this, only 41.17% reported receiving information of this sort after their participation. Research participation is a strong interest of PHA patient constituents; clear and consistent communication from the research team is an expectation of many participants. Despite this expectation, 58.83% of respondents indicated they did not receive communication from the research team after participation. This offers an opportunity not only to improve participants' experiences but also to increase the likelihood of future study participation.